Ramadan Fasting and NCDs-Example of the Diabetes - Bencharif, Meriem; Sersar, Ibrahim; Bentaleb, Maroua; Boutata, Fatima Zohra; Benabbas, Youcef (Frontiers in Nutrition, 2022)
Although Ramadan lasts only for one month each year, it can be accompanied by significant changes in: both energy and nutritional intake; in the diet composition; in the working hours; and the usual way of life. Despite this religious tolerance, many faithful who are eligible for the exemption observe the fast of Ramadan. The world is experiencing an increase in the emergence of non-communicable diseases (NCDs). Environmental and behavioral risk factors related to lifestyle, such as smoking, excessive alcohol consumption, unhealthy diet and sedentarity have a causal association with NCDs. Diabetes is one of the highest prevalent NCDs in the world and it continues increasing year by year. This chronic disease can lead to significant potential complications (degenerative, dermatological and acute) to the patient’s health. This requires an individual and appropriate care, both dietetic and therapeutic and over the long term will at best make it possible to sensitize the diabetic patient to the adverse effects related to his disease and thus improve its quality of life. Performing the Fast of Ramadan for a diabetic is a common situation. Diabetes is the only chronic disease widely studied in relation to Ramadan fasting. In the literature, many studies have investigated the effects of Ramadan intermittent fasting on diabetic patients. This article aims to provide a general overview and highlight if there are many effect of Ramadan fasting on diabetes, as an example of a NCDs.